2017
DOI: 10.1080/07420528.2017.1374286
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sunlight exposure on hospitalization in emergency psychiatry

Abstract: Excessive sunlight exposure may exert a fundamental role on psychopathological conditions presumably affecting biological vulnerability. A better understanding of its effect on the course of bipolar and other psychiatric disorders may assist in tailoring the adequate treatment for patients resulting in a shorter stay within hospitalized settings and a better treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…In line with our hypothesis, the first significant finding consisted in the increased amount of bipolar subjects’ admissions when the mean sunshine hours was longer. This result confirms the role of meteorological variables such as sunshine hours on the admission rates of bipolar subjects when using a different methodology rather that that used in previously published studies [14,16], suggesting that the photoperiod reaches its maximum extension during summer and its minimum during winter in Italy. Importantly, increased sunlight exposure during the day has been hypothesized to play a stabilizing effect on specific neurotransmitters levels such as monoamines that are relevant to mood disorders [6].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In line with our hypothesis, the first significant finding consisted in the increased amount of bipolar subjects’ admissions when the mean sunshine hours was longer. This result confirms the role of meteorological variables such as sunshine hours on the admission rates of bipolar subjects when using a different methodology rather that that used in previously published studies [14,16], suggesting that the photoperiod reaches its maximum extension during summer and its minimum during winter in Italy. Importantly, increased sunlight exposure during the day has been hypothesized to play a stabilizing effect on specific neurotransmitters levels such as monoamines that are relevant to mood disorders [6].…”
Section: Discussionsupporting
confidence: 84%
“…Several authors reported a positive association between the intensity of sunlight exposure and hyperthymic temperament [38], the intensity of sunlight exposure and manic/mixed onset of BD [14,16,22,24,25,39,40], although not all studies replicate these findings [17,18,41,42,43,44]. The opposing findings between studies using cross-sectional or prospective data (i.e., hospital admission records or self-report data) might probably be explained according to methodological differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If patients had more than one psychiatric diagnosis, the principal psychiatric condition as diagnosed by the treating psychiatrist, was recorded. According to previous published studies (33, 34), we grouped the diagnosis in four main categories: bipolar and related disorders, depressive disorders, schizophrenia, and related disorders, other psychiatric disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with Alzheimer's (AD) and Parkinson's disease exhibit sundowning phenomenon where they experience psychological and behavioral disturbances such as depressed mood, elevated anxiety, and heightened agitation during sunset (Bedrosian & Nelson, ). About 20% of the bipolar disorder (BD) patients demonstrate abnormal chronobiological rhythmicity and seasonal effect (Aguglia et al, ), especially with luminosity (Aguglia et al, ; Goikolea et al, ). Excessive sunlight exposure during spring/summer is reported to result in higher prevalence of hospitalization possibly due to impaired biological mechanisms such as dysregulation of serotonin/melatonin metabolism (Abreu & Bragança, ; Aguglia, Borsotti, & Maina, ; Geoffroy et al, ).…”
Section: Introductionmentioning
confidence: 99%